PP.05.11: ARTERIAL STIFFNESS IS INCREASED IN PATIENTS WITH DIABETES MELLITUS INDEPENDENT OF BP LEVELS. (June 2015) - Papakatsika, S.; Antza, C.; Dimopoulos, C.; Mikoudi, K.; Stabouli, S.; Kotsis, V.
Abstract : Objective: The aim of this study was to indentify if patients with diabetes mellitus present increased arterial stiffness compared to non diabetic subjects. Design and method: 423 consecutive subjects (51.7% male) with age 38.5 ± 24.7 years were included in the study. Subjects were never treated before for hypertension. A physician measured CBP three times in each subject using a mercury sphygmomanometer. All the subjects underwent 24h-ABPM on a usual working day. Pulse wave velocity (PWV) was measured after 15 min of rest in the supine position. The subject was not speaking or sleeping in a quiet, semi-darkened, temperature-controlled laboratory. Participants had advised to refrain from eating, smoking and drinking caffeine beverages and alcohol before measurement. PWV was calculated as the transit time of the arterial pulse along the carotid-femoral distance divided with the distance that measured directly. Results: Carotid- femoral PWV was independently associated (ANCOVA analysis) with age (B = 0.098, P < 0.001), 24 h average SBP (B = 0.058, P < 0.000) and presence of diabetes mellitus (B = 1.7, P = 0.0003), but not with office BP values, 24 h DBP, 24 SD SBP, 24 h SD DPB and 24 h PP. Carotid-femoral PWV was found 10.073 ± 0.133 (SE) in patients without diabetes and 11.773 ± 0.545 (SE) m/sec in patients with diabetes after adjustment for age, gender, office BP, 24 h SBP, 24 h DBP, 24 h pulse pressure, and 24 h BP SDs. The difference in carotid- femoral PWV between non diabetic and diabetic patients was -1.700 ± 0.566 (SE). This difference was statistically significant at the 0.01 level after Bonferroni's adjustment for multiple comparisons. Conclusions: Arterial stiffness was found increased in patients with diabetes mellitus suggesting a role for diabetes in the large arteries arteriosclerosis independent of age, gender and blood pressure levels.